Personality Traits, Remote Work and Productivity - Nicolas Gavoille; Mihails Hazans (Institute of Labor Economics (IZA), 2022)
The future of teleworking ultimately depends on its impact on workers' productivity and wellbeing, yet the effect of remote working on productivity is not well understood. This paper investigates the link between personality traits and workers' productivity when working from home. We exploit a survey providing measures of the "Big Five" personality traits for more than 1700 recent teleworkers. We document strong links between personality, productivity, and willingness to work from home post-pandemic. Ceteris paribus, Conscientiousness and Openness to Experience are positively associated with a higher productivity from home, especially for females. On the other hand, the link between Extraversion and preference for teleworking is negative. These results suggest that a one-size-fits-all policy is unlikely to maximize neither firms' productivity nor workers' satisfaction.
Keywords: J24; J32; J81; 330; personality traits; teleworking; work from home; productivity; COVID-19